Crowdsourcing Criminology: Social Media and Citizen Policing in Missing Person Cases. (December 2019) - Gray, Garry; Benning, Brigitte
Criminology is undergoing a process of innovation and experimentation with the rise of social media. Although police have traditionally been the locus of legal enforcement, ordinary citizens are increasingly afforded opportunities to participate in crowdsourced investigations. In this article, we explore the emerging field of crowdsourcing criminology and its relationship to newsmaking criminology, public criminology, and the reshaping of news as infotainment (popular criminology). Drawing on a case study of a missing person named Emma Fillipoff, and our experience of involvement in the development of a television (TV) documentary dedicated to help finding Emma, we examine the process of crowdsourcing in practice and how it may oscillate between infotainment and public criminology inspired by academic evidence. Crowdsourcing criminology represents both a theoretical and an applied shift in our research focus and paves the way for a host of new projects that strive to reveal the strategies and techniques that define and characterize crowdsourced investigations.